Should They Stay or Should They Go Now? The Discretionary Character of Poor Relief, Settlement and Removal in the Low Countries - Schepers, Marjolein (BMGN - Low Countries Historical Review, 2018)
Poor migrants in early modern Europe were often sent away to their place of origin to prevent them from becoming a burden on their place of residence. The laws of ‘settlement’ determined to which place they had to return to apply for poor relief. Despite increasing centralisation, and even the introduction of national legislation in the nineteenth century, settlement remained framed within the local parish or municipality. This paper argues that continuity existed in local belonging and the autonomy of local communities in negotiations on the removal of migrants. It analyses why some migrants were ‘removed’ and others were not, and to which extent and why local communities deviated from legislation. Analysing case studies of eighteenth-century Flanders, which have been particularly well documented, helps to place the predominantly anglocentric historiography on settlement and removal in a broader framework and also helps to further our understanding of the systems of inclusion and exclusion of migrants. This article is part of the special issue ’Political Change and Civic Continuities in the Age of Revolutions’. Arme migranten werden in vroegmodern Europa vaak weggezonden naar hun plaats van herkomst, opdat zij niet ten laste van hun woonplaats zouden vallen. In de wetten van onderstandswoonst, ook wel onderstandsdomicilie genoemd, werd bepaald naar welke plaats zij teruggezonden moesten worden. Hoewel er toenemende centralisering plaatsvond en er in de negentiende eeuw nationale wetgeving hierover werd ingevoerd, bleef onderstandswoonst gekaderd in de lokale parochie of gemeente. Dit paper betoogt dat er continuïteit bestond in het thuishoren in de lokale gemeenschap (belonging) en dat er lokale autonomie bleef bestaan in het beslissingsmakingsproces over wie uitgesloten werd en wie niet. Het artikel onderzoekt expliciet waarom sommige migranten werden teruggezonden en andere niet, en in welke mate en waarom lokale gemeenschappen hierin het heft in eigen handen namen en afweken van de regelgeving. De analyse van uitzonderlijk goed gedocumenteerde case studies uit achttiende-eeuws Vlaanderen helpt de voornamelijk anglocentrische historiografie over settlement en removal in een breder kader te plaatsen en meer in het algemeen om de systemen van in- en uitsluiting van migranten beter te begrijpen. Dit artikel maakt deel uit van het themanummer ’Political Change and Civic Continuities in the Age of Revolutions’.